New species of Amphipoda (Crustacea: Peracarida) from the Solitary Islands, New South Wales, Australia - Hughes, Lauren E.; Lowry, James K. (Zootaxa, 2006)
Nine new species of epibenthic amphipods are described from the Solitary Islands, mid-north coast, New South Wales, Australia. Material was collected on natural habitats and from a range of small plastic artificial substrates. Protohyale pusilla (Chevreux, 1907) is reported from Australia for the first time. The subgenus Telsosynopia Karaman, 1986 is given generic status and Regalia juliana Lowry & Springthorpe, 2005 is transferred to Tepidopleustes in the pleustid subfamily Austropleustinae. New species include: Protohyale solitaire sp. nov. (Hyalidae); Ericthonius rodneyi sp. nov. and Ericthonius forbesii sp. nov. (Ischyroceridae); Liljeborgia polonius sp. nov. (Liljeborgiidae); Elasmopus arrawarra sp. nov. and Hoho cornishi sp. nov. (Melitidae); Gammaropsis legoliath sp. nov. (Photidae); Tepidopleustes coffsiana sp. nov. (Pleustidae); and Telsosynopia trifidilla sp. nov. (Synopiidae).